The Digital Preservation of Seloko Tradition Adat Jambi : The Snapshot of Challenges, Struggles and Gaps (Universitas Terbuka, 2023)
Jambi Province is one of many provinces in Indonesia which has same cultural heritage as Malay with its original culture, this made the Government of Jambi Province want to preserve the Malay culture as the identity of Jambi, one of the traditions is Seloko. Jambi Malay traditional Seloko is the expressions that contain messages, advice, tips, and valuable advice morals, as well as a means of coercion and norms which used proverbs, words, pantun and figurative words. The purpose of this article are to describe the digital preservation of Seloko Adat Tradition in Jambi which is rarely to fine nowadays, it describes the challenges, struggles and gaps with the expertise related to this area. The method of the research is descriptive analytical study along with the observations concerning digital preservation support available. The digital preservation in this article delivers the snapshot of the government, academician, librarian, community, language office and Lembaga Adat already done in order to maintain the collection so everyone can learn and study about the Seloko Tradition Adat in Jambi Province.